Television Advertising Factors and Socio-Psychological Influences on Consumer Attitudes and Purchase Intentions For FMCG Products in Bangladesh - Mohammad Toufiqur Rahman (Universiti Sains Islam Malaysia, 2025)
Matric: 4150208 (FEM)-Restricted until Aug 2028